SECTORAL INDEX RETURN PREDICTABILITY –PREDICTING POWER OF INDEX VALUATION RATIOS - R, Naveen Kumara; Dr K Ramesh (The journal of contemporary issues in business and government, 2021)
The paper examines sectoral return predictability for eleven sectoral indices of National Stock Exchange (NSE). The article shows that investors can predict the movement of sectoral indices using the index valuation ratios of those sectors. A predictive regression using the index valuation ratios as predictor variables was run for each sector using Generalized Methods of Moments (GMM). Lagged dependent variables were used as instruments to solve the problem of endogeneity. The study also uses Newey-West (HAC) correction to get unbiased coefficients. The index valuation ratios predict the returns in nine out of eleven sectors for the sample period running from 2005 to 2019. The findings assist individual investors and fund managers to forecast the sectoral returns and develop an informed trading strategy to maximize returns and diversify their portfolio to minimize the loss.